ANALISIS KARAKTERISTIK KEWIRAUSAHAAN DAN ADOPSI INOVASI PETANI KOPI DI PROVINSI LAMPUNG - Burhanuddin Burhanuddin; Rachmat Pambudy; Ach Firman Wahyudi (Jurnal Agribisnis Indonesia, 2018)
Lampung Province is one of the coffee producing. This is because the topology of the region is very suitable for the fertility of coffee plants. The majority of coffee farmers in Indonesia carry out farming activities in rural areas with small business scale and limited access to innovation, capital, management, technology and information. One factor that causes farmers to be competitive in the context of entrepreneurship at the farmer level is the lack of entrepreneurial skills for farmers, so farmers who are engaged in the agribusiness sector, especially in the upstream subsystem, are very difficult to align with an entrepreneur in the non-agribusiness sector. The lack of entrepreneurial character and entrepreneurial capacity such as entrepreneurial skills is what causes farmers to be less competitive, which results in the agribusiness sector not being able to develop optimally. Adoption of farmers to agricultural technology is determined by their need for the level of technology offered and the suitability of technology for environmental, biophysical, and socio-cultural conditions in an area. The purpose of this study was to determine the general description and profile of Lampung coffee farmers, to find out the entrepreneurial characteristics of Lampung coffee farmers, and to analyze the characteristics, channels and stages of adoption of innovative Lampung coffee farmers with 160 respondents. This research was conducted in West Lampung and Tanggamus is the center of coffee production in Indonesia. The type of data were primary and secondary data. The data analysis method were the method of qualitative and quantitative analysis. The results showed that the dominant character of coffee farmer entrepreneurship is Commitment, Seeking feedback, Integrity and realiability, and Tolerance for failure. Innovation is considered to provide convenience, more suitable, easy to practice, and easily monitored for its development and is not difficult to imitate. Coffee farmers are open to innovation and benefit from the innovation. Coffee farmers use their innovation channels effectively. The entrepreneurial character of farmers correlates with innovation channel variables and stages of innovation adoption. Independent personality and Managerial Skill for Entrepreneurs (MSE) characters correlate with three innovation channel variables and Creativity and innovativeness (CAI) character correlates with all stages of innovation adoption variables.